Pengaruh Lama Perendaman Air Perasan Buah Belimbing Wuluh (Averrhoa bilimbi Linn) terhadap Karakteristik Udang Vaname (Litopenaeus vannamei) pada Suhu Ruang - Saraswati Rahayu, Ni Kadek; Sugitha, I Made; Hatiningsih, sayi (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 11 No 3 (2022): Jurnal ITEPADO - 10.24843/itepa.2022.v11.i03.p08, 2022)
This study aims to determine the effect of immersion time in wuluh starfruit juice (Averrhoa bilimbi Linn) on characteristics vaname shrimp (Litopenaeus vannamei) as well as to determine the right time of immersion in wuluh starfruit juice to produce vaname shrimp the best characteristics. The experimental design used in this study was a Completely Randomized Design with 5 level immersion treatments, namely: 0 minutes, 20 minutes, 40 minutes, 60 minutes, and 80 minutes. The treatment was repeated 3 times to obtain 15 experimental units. The data obtained were analyzed by variance (ANOVA) and if the treatment effected the observed variables then it was continued with the Duncan Multiple Range Test (DMRT). The duration of immersion time vaname shrimp in wuluh starfruit juice was 20 minutes produced the best characteristic vaname shrimp, water content is 82.23%, the acidity was 6.77, the microbial total 4.98 Log CFU/g and histamine was 0.1 ppm, color and connected segment liked with scor the brightness a bit lost, inter-segment less firm, smell liked, texture liked with scor less elastic, compact and dense, and overall acceptance liked.